Mitochondrial genome assembly of the Chinese endemic species of Camellia luteoflora and revealing its repetitive sequence mediated recombination, codon preferences and MTPTs - Xu Xiao; Zhaohui Ran; Chao Yan; Weihao Gu; Zhi Li (BMC Plant Biology)
Abstract Camellia luteoflora Y.K. Li ex Hung T. Chang & F.A. Zeng belongs to the Camellia L. genus (Theaceae Mirb.). As an endemic, rare, and critically endangered species in China, it holds significant ornamental and economic value, garnering global attention due to its ecological rarity. Despite its conservation importance, genomic investigations on this species remain limited, particularly in organelle genomics, hindering progress in phylogenetic classification and population identification. In this study, we employed high-throughput sequencing to assemble the first complete mitochondrial genome of C. luteoflora and reannotated its chloroplast genome. Through integrated bioinformatics analyses, we systematically characterized the mitochondrial genome’s structural organization, gene content, interorganellar DNA transfer, sequence variation, and evolutionary relationships.Key findings revealed a circular mitochondrial genome spanning 587,847 bp with a GC content of 44.63%. The genome harbors70 unique functional genes, including 40 protein-coding genes (PCGs), 27 tRNA genes, and 3 rRNA genes. Notably, 9 PCGs contained 22 intronic regions. Codon usage analysis demonstrated a pronounced A/U bias in synonymous codon selection. Structural features included 506 dispersed repeats and 240 simple sequence repeats. Comparative genomics identified 19 chloroplast-derived transfer events, contributing 29,534 bp (3.77% of total mitochondrial DNA). RNA editing prediction revealed 539 C-to-T conversion events across PCGs. Phylogenetic reconstruction using mitochondrial PCGs positioned C. luteoflora in closest evolutionary proximity to Camellia sinensis var. sinensis. Selection pressure analysis (Ka/Ks ratios < 1 for 11 PCGs) and nucleotide diversity assessment (Pi values: 0–0.00711) indicated strong purifying selection and low sequence divergence.This study provides the first comprehensive mitochondrial genomic resource for C. luteoflora, offering critical insights for germplasm conservation, comparative organelle genomics, phylogenetic resolution, and evolutionary adaptation studies in Camellia species.